(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In recent days, the creation of novel drug delivery mechanisms utilising nanoparticles has been of exponential importance. Innovative techniques for synthesising nanoparticles are very relevant for nanotechnology and nanoscience growth. Nanoparticles, according to their size, type, material properties, may be divided into any of the different forms. It’s have various properties of nanoparticles. Nanotechnology is a modern field of science which plays a crucial role in day to day life aspects. Nanotechnology refers to the development, processing usage of nanometer-sized materials. This review focuses on properties of nanoparticles, characterisation of nanoparticles health perspectives.